RETAINING CUSTOMER LOYALTY IN ONLINE SHOPPING. A COMPARISON OF UK WITH RUSSIA - Zimina, Olga (2006)
This study examines the retention of customer loyalty in online shopping and provides information on the UK and Russian markets and explains the differences between them. First, it gives an overview of the whole process of investigation. Secondly, it examines the customer loyalty concept in online shopping. Next, it reviews the profiles of the UK and Russia and their online markets. A quantitative research in the form of the email questionnaire for each country was conducted and the results are analysed. Finally, the conclusions of the study are reported with reference to each objective. This is followed by the limitations, and concludes with some suggestions for further research.